Movement of Fluid Inside the Sphere - Abenov, Ðœ.Ðœ.; Gabbassov, Ðœ.B.; Ismagulova, F.Y. (International Journal of Engineering and Technology, 2018)
The paper presents an exact analytical solution of the stationary problem of an incompressible ideal fluid flow inside a sphere under the action of an external potential mass force.